1997
DOI: 10.1111/j.1469-7793.1997.613bg.x
|View full text |Cite
|
Sign up to set email alerts
|

Two components of blood‐brain barrier disruption in the rat

Abstract: 1. Permeability of pial venular capillaries to Lucifer Yellow (PLY) was measured using the single microvessel occlusion technique. 2. PLY was extremely low, when measured shortly after the removal of the meninges, consistent with an intact blood-brain barrier, but rose spontaneously to (1·65 ± 0·60) ² 10¦É cm s¢ (mean ± s.d.) within 20-60 min. This first phase of spontaneous disruption lasted 44-164 min. A second phase started when PLY rose sharply, and was characterized by rapid permeability fluctuations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
51
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 24 publications
12
51
1
Order By: Relevance
“…Application of 1 mÒ oleic had no permeability-increasing effect. Rapid changes in permeability (as previously reported by Easton, Sarker & Fraser, 1997) were found to be related to the concentration of arachidonic acid ( Fig. 1B and C).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Application of 1 mÒ oleic had no permeability-increasing effect. Rapid changes in permeability (as previously reported by Easton, Sarker & Fraser, 1997) were found to be related to the concentration of arachidonic acid ( Fig. 1B and C).…”
Section: Resultssupporting
confidence: 56%
“…We found that focally administered arachidonic acid dose-dependently and reversibly increased pial venular capillary permeability to Lucifer Yellow, and that these increases could be very large, consistent with the formation of cerebral oedema. Previously, a high permeability state that had been induced by craniotomy (Easton et al 1997), and in which free radical generation had been implicated, showed a characteristic flickering, not seen at lower permeabilities. As arachidonic acid, in the present series of experiments, also often resulted in a flickering permeability response, not limited to high permeabilities, the idea of free radical formation was raised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the microvessels chosen were post-capillary venules of 15-40 μm diameter for the permeability measurement, and around 1/4 of the microvessels were capillaries. 24,35 The reasons that we currently only measured the permeability of post-capillary venules and capillaries were: 1) to avoid the influence of smooth muscle cells at arteries, arterioles, and large venules, which would contract under stimuli and affect the permeability measurement; 35 2) our previous studies on the BBB permeability were also conducted on this type of post-capillary venules. 23,24 The permeability was determined off-line from the pre-collected images by using ImageJ (National Institutes of Health, Bethesda, MD, USA).…”
Section: Determination Of the Bbb Solute Permeabilitymentioning
confidence: 99%
“…Postcapillary venules and capillaries were suggested to be more suitable for permeability study since they are relatively less contractible or expandable under stimulations. 35 These properties are necessary for accurate determination of the BBB permeability under FUS stimulations. 35 Finally, their method can only give a relative permeability index, not the true solute permeability for a microvessel defined by the KedemKatchalsky equation.…”
mentioning
confidence: 99%